Ansible : up & running, automating configuration management and deployment the easy way - Meijer, Bas; Hochstein, Lorin; Moser, René (O'Reilly Media, Incorporated, 2022)
Among the many configuration management tools available, Ansible has some distinct advantages: It's minimal in nature. You don't need to install agents on your nodes. And there's an easy learning curve. With this updated third edition, you'll quickly learn how to be productive with Ansible whether you're a developer deploying code or a system administrator looking for a better automation solution. Authors Bas Meijer, Lorin Hochstein, and Rene Moser show you how to write playbooks (Ansible's configuration management scripts), manage remote servers, and explore the tool's real power: built-in declarative modules. You'll learn how Ansible has all the functionality you need--and the simplicity you desire. Explore Ansible configuration management and deployment Manage Linux, Windows, and network devices Learn how to apply Ansible best practices Understand how to use the new collections format Create custom modules and plug-ins Generate reusable Ansible content for open source middleware Build container images, images for cloud instances, and cloud infrastructure Automate CI/CD development environments Learn how to use Ansible Automation Platform for DevOps.